Amelioration of muscle wasting by glucagon‐like peptide‐1 receptor agonist in muscle atrophy. Issue 4 (24th April 2019) - Hong, Yeonhee; Lee, Jong Han; Jeong, Kwang Won; Choi, Cheol Soo; Jun, Hee‐Sook
Abstract: Background: Skeletal muscle atrophy is defined as a reduction of muscle mass caused by excessive protein degradation. However, the development of therapeutic interventions is still in an early stage. Although glucagon‐like peptide‐1 receptor (GLP‐1R) agonists, such as exendin‐4 (Ex‐4) and dulaglutide, are widely used for the treatment of diabetes, their effects on muscle pathology are unknown. In this study, we investigated the therapeutic potential of GLP‐1R agonist for muscle wasting and the mechanisms involved. Methods: Mouse C2C12 myotubes were used to evaluate the in vitro effects of Ex‐4 in the presence or absence of dexamethasone (Dex) on the regulation of the expression of muscle atrophic factors and the underlying mechanisms using various pharmacological inhibitors. In addition, we investigated the in vivo therapeutic effect of Ex‐4 in a Dex‐induced mouse muscle atrophy model (20 mg/kg/day i.p.) followed by injection of Ex‐4 (100 ng/day i.p.) for 12 days and chronic kidney disease (CKD)‐induced muscle atrophy model. Furthermore, we evaluated the effect of a long‐acting GLP‐1R agonist by treatment of dulaglutide (1 mg/kg/week s.c.) for 3 weeks, in DBA/2J‐mdx mice, a Duchenne muscular dystrophy model. Results: Ex‐4 suppressed the expression of myostatin (MSTN) and muscle atrophic factors such as F‐box only protein 32 (atrogin‐1) and muscle RING‐finger protein‐1 (MuRF‐1) in Dex‐treated C2C12 myotubes. The suppression effect was via protein kinase A and protein kinase B signalling pathways through GLP‐1R. In addition, Ex‐4 treatment inhibited glucocorticoid receptor (GR) translocation by up‐regulating the proteins of GR inhibitory complexes. In a Dex‐induced muscle atrophy model, Ex‐4 ameliorated muscle atrophy by suppressing muscle atrophic factors and enhancing myogenic factors (MyoG and MyoD), leading to increased muscle mass and function. In the CKD muscle atrophy model, Ex‐4 also increased muscle mass, myofiber size, and muscle function. In addition, treatment with a long‐acting GLP‐1R agonist, dulaglutide, recovered muscle mass and function in DBA/2J‐mdx mice. Conclusions: GLP‐1R agonists ameliorate muscle wasting by suppressing MSTN and muscle atrophic factors and enhancing myogenic factors through GLP‐1R‐mediated signalling pathways. These novel findings suggest that activating GLP‐1R signalling may be useful for the treatment of atrophy‐related muscular diseases.